2003
DOI: 10.1007/s00216-002-1723-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative on-line high-resolution NMR spectroscopy in process engineering applications

Abstract: In many technical processes, complex multicomponent mixtures have to be handled, for example, in reaction or separation equipment. High-resolution NMR spectroscopy is an excellent tool to study these mixtures and gain insight in their behavior in the processes. For on-line studies under process conditions, flow NMR probes can be used in a wide range of temperature and pressure. A major challenge in engineering applications of NMR spectroscopy is the need for quantitative evaluation. Flow rates, recovery times,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…For the 13 C NMR spectra, this is only the case if certain conditions regarding the relaxation in the experiments are fulfilled, cf. [6][7][8]. This was the case here.…”
Section: Methodsmentioning
confidence: 57%
See 1 more Smart Citation
“…For the 13 C NMR spectra, this is only the case if certain conditions regarding the relaxation in the experiments are fulfilled, cf. [6][7][8]. This was the case here.…”
Section: Methodsmentioning
confidence: 57%
“…Recently developed methods for quantitative online NMR spectroscopy allow gaining new insight in reacting multicomponent mixtures [6][7][8]. By NMR spectroscopy, even chemically similar components can be distinguished and their nature and concentration can be determined.…”
Section: Introductionmentioning
confidence: 99%
“…NMR diagnostics NMR is a strong diagnostic tool and especially useful to probe the pH [43,44], temperature [45], and flow dynamics occuring during a separation [46,47] which are not observable with most other detectors. The ability of NMR to study the cITP process has been demonstrated previously [48].…”
Section: Chiral Separation With Citp-nmrmentioning
confidence: 99%
“…Thus it is a promising quantitative technique without elaborate calibration. Various theoretical and experimental papers have dealt with quantitative NMR spectroscopy, e.g., with respect to continuous flow [3,4], in agriculture [5], for trace components [6] or process engineering or pharmaceutical chemistry applications [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%